Marrakech Treaty: A look from the public libraries of Portoviejo - Cevallos Alcívar, Lida Julexy; Arteaga Tejena, Gema Nicole; Molina Arteaga, Karol Denisse; Quindemil Torrijo, Eneida Maria; Rumbaut León, Felipe (Revista General de Información y Documentación, 2024)
The Marrakesh Treaty is an international agreement whose purpose is to facilitate access to published works for people with visual disabilities or print difficulties. In the particular case of Ecuador, the commitments were officially ratified since 2016. This fact was considered a significant event that began a renewed approach to Intellectual Property in the country. The objective of the research was to propose a strategic plan to facilitate access to works in accessible formats in Manabi public libraries in accordance with the provisions of the Marrakech Treaty. The study had a qualitative approach, with a descriptive scope. To obtain information, the interview technique was used, which allowed collecting statements from librarians, with the purpose of determining the degree of adherence to the provisions of the Marrakech Treaty in the public libraries subject to analysis. The results showed that access to information as an essential human right allows participation and knowledge in society. In this sense, the Marrakesh Treaty seeks to facilitate the accessibility of works in accessible formats for people with visual disabilities. Despite challenges in public libraries in Ecuador, their legal commitment is highlighted and a strategic plan is proposed to promote inclusion and equal access to knowledge for people with visual disabilities.